Genetic basis of rheumatoid disease: HLA antigens, disease manifestations, and toxic reactions to drugs. Issue 6148 (11th November 1978) - Panayi, G S; Wooley, P; Batchelor, J R
Abstract : Ninety-five patients with rheumatoid arthritis and 200 healthy controls were examined for HLA-D-related (HLA-DR) alloantigens. HLA-DRW4 was significantly more prevalent among the patients and was particularly common in those with a family history of the disease (77% of such patients had DRW4 compared with 34% of controls). Significantly fewer patients than controls had DRW2: patients with this antigen had rheumatoid nodules less frequently and significantly lower titres of rheumatoid factor than patients without DRW2. In contrast DRW3 was significantly more prevalent among severely affected patients with rheumatoid factor titres exceeding 1/1280 and in patients with nodules. There was a significant association between DRW2 and DRW3 and toxic reactions to sodium aurothiomalate and penicillamine. The results suggest that the HLA-DR phenotype is associated not only with susceptibility to rheumatoid arthritis but also with severity of the disease and whether certain toxic reactions to drugs occur.